Computational Studies of Confined Submerge Fan to Circulate and Oxygenate Hypolimnetic Layer in Hydro Power Reservoirs - Mushtaq, Muhammad Umar; Sanaullah, Khairuddin; Henry Rigit, Andrew Ragai; Khan, Afrasyab; Ramji, Harunal Rejan (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
The oxygen level is deficient at the depth of the lakes or reservoirs due to thermal stratification. Due to deficient oxygen level at the bottom of thermal stratified lakes, the reduction reactions occur that form hydrogen sulphide, iron, phosphorous and other compounds which are harmful to the water quality, fish life as well as dam or reservoir structures and other species. Hypolimnetic aeration and oxygenation systems can be used for this purpose to prevent the formation of harmful substances. A prototype design of submerged fan will be used to penetrate at maximum depth of the lakes or reservoirs and find the velocity of the submerged fan through CFD simulations.